MEDIA PEMBELAJARAN ILMU PENGETAHUAN SOSIAL BERBASIS APLIKASI MOBILE LEARNING BAGI SISWA SEKOLAH DASAR - Imaniar Purbasari; Erik Aditia Ismaya; Nunuk Suryani; Djono Djono (Universitas Negeri Malang, 2019)
Tujuan penelitian yaitu mendeskripsikan produk dan menjelaskan penggunaan media pembelajaran IPS berbasis aplikasi mobile learning dengan pendekatan social constructivism yang dihasilkan bagi siswa sekolah dasar. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi pustaka serta jenis penelitian deskriptif. Data utama diperoleh dari buku, jurnal, artikel, dan catatan harian penelitian. Hasil penelitian yakni media pembelajaran IPS berbasis aplikasi mobile learning yang dihasilkan bagi siswa sekolah dasar berupa komik, gambar berseri, dan poster yang dikemas dalam program Edmodo. Edmodo merupakan aplikasi yang menarik dengan elemen sosial berupa aplikasi edukasi berbasis jejaring sosial. Akun Edmodo dapat dibuat oleh guru, siswa dan orang tua yang berbasis cloud kolaborasi dengan aplikasi yang cukup aman digunakan untuk kelompok terbatas. The objective of the research is to describe the learning media product learning of social studies based on mobile learning application with social constructivism approach which is produced for elementary school students and explain the use of social studies learning media based on mobile learning application with social constructivism approach for elementary school students. This research uses qualitative approach with literature study method and descriptive research type. The main data were obtained from books, journals, articles, and research diaries. The result of research is learning media of social studies based on mobile learning application that produced for elementary school students in the form of comics, serial images, and posters that are packed in Edmodo program. The resulting comic tells the economic activities carried out by the characters. The resulting image contains the sub subject matter of globalization around me. The learning consists of content of social studies subjects (globalization), sains (energy change) and Indonesian (using standard and coherent vocabulary). Edmodo is an interesting application with social elements in the form of educational applications based on social networking. Edmodo accounts can be created by collaborative cloud-based teachers, students and parents with applications that are safe enough to use for restricted groups. Groups created by teachers, students and parents can sign in with a dedicated account. Teachers provide learning tools as well as learning process planning. Students and parents can access learning wherever and whenever. Students are able to establish social interaction with friends in groups or teachers as a form of discovery and discussion of knowledge. Parents as controlling the access and implementation of learning by students. DOI: http://dx.doi.org/10.17977/um020v13i12019p97